2017
DOI: 10.3791/56196
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Cooling-induced Deactivations to Study Cortical Contributions to Obstacle Memory in the Walking Cat

Abstract: On complex, naturalistic terrain, sensory information about an environmental obstacle can be used to rapidly adjust locomotor movements for avoidance. For example, in the cat, visual information about an impending obstacle can modulate stepping for avoidance. Locomotor adaptation can also occur independent of vision, as sudden tactile inputs to the leg by an expected obstacle can modify the stepping of all four legs for avoidance. Such complex locomotor coordination involves supraspinal structures, such as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…During this time, the obstacle was covertly removed from the walkway before locomotion resumed. In comparison to obstacle-absent trials (OA), elevated hindleg stepping observed during OP continuation demonstrated the ability of animals to remember the obstacle over which the forelegs stepped ( Figure 1B) [4,8,9].…”
Section: Modulated Ppc Activity During Wm-guided Obstacle Negotiationmentioning
confidence: 98%
See 2 more Smart Citations
“…During this time, the obstacle was covertly removed from the walkway before locomotion resumed. In comparison to obstacle-absent trials (OA), elevated hindleg stepping observed during OP continuation demonstrated the ability of animals to remember the obstacle over which the forelegs stepped ( Figure 1B) [4,8,9].…”
Section: Modulated Ppc Activity During Wm-guided Obstacle Negotiationmentioning
confidence: 98%
“…Obstacle WM was assessed by comparing obstructed (OP) with unobstructed (OA) locomotion using the same apparatus described previously [8][9][10]. In OP trials, each animal approached and stepped over a 25.8 cm wide x 8.7 cm high x 3 mm thick obstacle raised onto the surface of the walkway ( Figure 1A).…”
Section: Behavioral Paradigmmentioning
confidence: 99%
See 1 more Smart Citation
“…The same apparatus described in Wong et al (2016), Wong and Lomber (2017) was used to assess visual and tactile obstacle working memory in the present study. Each cat was trained to walk along an 8-foot long runway.…”
Section: Apparatusmentioning
confidence: 99%